172k views
1 vote
Pretest: Unit 3

Question 16 of 20
For R(x) = 4x + 2 and g(x) = x2 - 6, find (f+g)(x).
A. 4x3 - 4
B. x2 + 4x - 4
O c. 4x2 - 16
O D. x2 + 4x+8
BMI

User Jon Gear
by
6.1k points

1 Answer

3 votes

Answer:

(f + g)(x) = x² + 4x - 4B

Explanation:

Let us solve the question

f(x) = 4x + 4

g(x) = x² - 6

→ We need to find (f + g)(x) which means f(x) + g(x)

(f + g)(x) = f(x) + g(x)

f(x) + g(x) = (4x + 2) + (x² - 6)

∴ f(x) + g(x) = 4x + 2 + x² - 6

→ Add the like terms

∵ f(x) + g(x) = 4x + x² + (2 - 6)

∴ f(x) + g(x) = 4x + x² + (-4)

→ Remember (+)(-) = (-)

∴ f(x) + g(x) = 4x + x² - 4

→ Arrange the terms from greatest power of x

∴ f(x) + g(x) = x² + 4x - 4

(f + g)(x) = x² + 4x - 4

User Dan Rubio
by
6.2k points